Techno-economic evaluation of waste heat recovery by organic Rankine cycle using pure light hydrocarbons and their mixtures as working fluid in a crude oil refinery. (15th October 2018) - Varga, Z.; Csaba, T.
Highlights: Organic Rankine cycle for waste heat recovery at low temperature (<140 °C) was studied. Effect of composition of working fluids on the process parameters was investigated. Butanes and their mixtures showed better results than pentanes. Significant reduction in the carbon dioxide emissions was achieved. Abstract: This paper summarizes the results of a study aimed at using isobutane, butane, isopentane and pentane as working fluid of an organic Rankine cycle utilizing heat of an air cooler. Ranking of different working fluids based on the maximum achievable power output, cycle efficiency, heat recovery, required heat exchanger area, attainable CO2 emission reduction, and payback period was performed. By applying pure components, the extractable turbine power varied in the range of 452–678 kW and the CO2 emission reduction potential was in the range of 723–1085 t/y in which isobutane provided the best results. Economic calculation involving both the capital and operating expenditures was conducted, which showed that the estimated payback periods were between 3.4 and 4.6 years with the best result of butane. The results of calculations that were obtained by using working fluids composed from pairs of light hydrocarbons showed that the extractable turbine power was higher for mixtures of butanes than those for butanes/pentanes and pentane mixtures. Based on the payback period, the hydrocarbon mixtures were composed from isobutane/butane in 25:75 and 50:50, and butane/pentane in 75:25 mass ratios that can be applied as favourable working fluids.